A brief taxonomic revision of Physoptychis (Alysseae, Brassicaceae) - German, Dmitry A; Teki̇n Mehmet; Španiel, Stanislav; Marhold, Karol; Al-Shehbaz, Ihsan A. (Phytotaxa, 2016)
Physoptychis is recognized as a genus of two species: P. caspica, a relatively widespread in SW Asia, and P. haussknechtii, an endemic of inner Anatolia. Nomenclature of both taxa is updated, and three new synonyms are established. Of them, the poorly known Fibigia thesigeri and Vesicaria physiphora are proven to be conspecific with P. caspica, while the recently described P. purpurascens is found to be indistinguishable from P. haussknechtii. The approximate locus classicus of V. physiphora, hitherto unclear, is revealed, and the name is typified. Notes on the original material and typification of Crambe caspica [≡ Physoptychis caspica] are provided. Morphological characteristics and distribution of P. haussknechtii are updated.